Desarrollo de casos de estudio en base al sistema nacional interconectado de Ecuador para el análisis de sistemas eléctricos de potencia - Reinoso Acosta, Robinson Daniel (2022)
In this research project, the modeling of the Ecuadorian SNI was carried out to perform case studies considering information from CELEC-TRANSLECTRIC and the current Electrification Master Plan (PME) to obtain a model based on the topology of the single-line diagram of the SNI and proceed to model the zones exposed in the PME. DIgSILENT's PowerFactory software was used, where the characteristic elements of the SEP were included, in which simulations in permanent and transient regime can be obtained. To verify that the system modeled in PowerFactory is similar to the real SNI, the SNI transformers were loaded with values obtained from the CELEC-TRANSELECTRIC post-operational report for January 12, 2021. Similar transformer chargeability and voltage values were obtained in the SNI busbars with small variations and in some cases with errors greater than 5%, which demonstrates the uncertainty of the model. Then, case studies were designed for the analysis of power flow, stability and contingencies based on the review of references to determine the behavior of the SNI for the years 2022 and 2027. Finally, PowerFactory yielded busbar voltage values within CENACE normal operating limits (5%) for the power flow and contingency study. For the transient stability analysis, two cases were considered: failure in the Riobamba-Taday transmission line and the output of unit 2 of the San Francisco hydroelectric power plant, for which the system did not present stability problems. Finally, the modeled SNI was reduced to the 500 kV system by means of network equivalents.